Exploring attributions of causality for child undernutrition: Qualitative analysis in Lusaka, Zambia - Nakawala Lufumpa; Anna Lavis; Rishi Caleyachetty; Michael Henry; Sheena Kabombwe; Semira Manaseki‐Holland (Wiley, 2022)
Abstract Child undernutrition is responsible for 45% of all under‐five deaths in low‐ and middle‐income countries (LMICs) and numerous morbidities. Although progress has been made, high levels of child undernutrition persist in Zambia. Existing studies have explored primary caretakers' (PCs) explanatory models of child undernutrition in LMICs, without comparison with those of health care providers (HCPs). This paper examines and compares the perceived causes of child undernutrition among PCs and HCPs in Zambia. We conducted a qualitative study, using semistructured one‐to‐one and group interviews, with 38 PCs and 10 HCPs to explore their perceptions of child undernutrition and its perceived causes in Lusaka district, Zambia. Interview data were analysed with thematic analysis. Our findings indicate that PCs and HCPs in Lusaka district have divergent explanatory models of child undernutrition and perceive parental agency differently. In divergently framing how they conceptualise undernutrition and who is able to prevent it, these models underpin different attributions of causality and different opportunities for intervention. PCs highlighted factors such as child food preferences, child health, and household finances. Contrarily, HCPs stressed factors such as 'improper feeding', only highlighting factors such as wider economic conditions when these impacted specifically on health care services. One factor, identified by both groups, was 'inadequate mothering'. To accelerate the reduction of child undernutrition, interventions must address divergences between PCs and HCPs' explanatory models. Additionally, attention needs to be paid to how wider socio‐economic and cultural contexts not only impact childhood undernutrition but shape attributions of causality.